Estimation of effected radon released from Ktebban River, north Basrah city, by using CR-39 - al battat, munaf (Journal of King Abdulaziz University: Marine Sciences, 2024)
Abstract In this work, closed can technique is uses to estimate the radon and radium content in solid samples, the estimation of the radon concentration was between 9.46±2.29Bq.m-3 to 29.83±4.81Bq.m-3, so that the effective radium variation from 0.001 Bq.kg-1 to 0.004571 Bq.kg-1 since it was responsible for radon emanation in the air. These values considered as with the acceptable values worldwide with neighbors countries. The flux and exhalation per unit area and per unit mass arranged between 0.13Bq. m-2h-1 to 0.54Bq.m-2h-1 and 0.003Bq.m-2h-1 to 0.015Bq.m-2h-1 respectively. These values are lower than the reported worldwide limit which indicates. It is safe use sediments as building materials or other uses.